Optimization of Synthetic Glucose Oxidase Gene Using A Recombinant Combination Strategy in Pichia Pastoris GS115 - Melika Fasihi; S. Sh. Rahpeyma; Ali Asghar Karkhanei; Jamshid Raheb (Journal of Sciences, Islamic Republic of Iran)
Glucose oxidase (e.C1.1.3.4) is a flavoenzyme that catalyzes the oxidation of β-D-glucose to D-gluconolactone and hydrogen peroxide. The D-gluconolactone hydrolyzed spontaneously produces gluconic acid. Glucose oxidase has been widely used in chemical, food industries, and medicine. In this study, the glucose oxidase gene was identified in the chromosomal DNA of Aspergillus niger and isolated by PCR techniques. The glucose oxidase gene was then synthetically designed, optimized, cloned, and transferred into suitable hosts. The constructed clones were selected to modify the best production and combined promoter systems to produce glucose oxidase enzymes. In this design, the PCR product fragment was cloned into pPIC9 plasmids and transferred into Pichia pastoris GS115 by electroporation. The constructed strain was named pp.pPIC9/GOX. This strain was selected as a host for the other synthetic construct called pGAPZ/GOX. The strain pp.pPIC9/GOX was transformed as the host for the pGAPZ/GOX construct containing the glucose oxidase gene, which is controlled by the pGAPZa promoter with a self-inducing promoter and the newly constructed strain named pp.pPGAPZ/PIC9/GOX. The expression and comparison of the glucose oxidase activity were investigated by combining methanol and self-induction promoter in both pp.pPIC9/GOX and pp.pPGAPZ/PIC9/GOX strains simultaneously, which led to higher glucose oxidase gene activity in the new strain. Using the methanol induction promoter with the simultaneous expression of self-induction promoter in separate constructs and same strains increased the glucose oxidase gene activity.